Design and Implementation of an IoT-Based Temperature and Humidity Monitoring System for Soil and Air using ESP32 on Non-Hydroponic Plants - Nindy Gaby Sepang; Keith Francis Ratumbuisang; Josua Setdefit Tambanaung; Yeheskiel Kamasi (JST (Jurnal Sains dan Teknologi), 2025)
The agricultural sector is increasingly confronted with serious challenges arising from climate variability, resource limitations, and the growing demand for sustainable food production. This study aims to design and evaluate an Internet of Things (IoT) based monitoring system for soil-based cultivation to address the lack of affordable and real-time environmental monitoring solutions for traditional farmers. Specifically, the research focuses on the design and implementation of an IoT-based system for monitoring soil and air temperature as well as soil moisture in non-hydroponic crops using an ESP32 microcontroller. This study adopts an applied research approach with a mixed-methods design, integrating quantitative sensor validation and system performance testing with qualitative assessments of system usability. The system was developed using an ESP32 microcontroller, a capacitive soil moisture sensor, a DS18B20 soil temperature sensor, and a DHT22 sensor for air temperature and humidity. Data were displayed locally on a 20×4 LCD and remotely via an ESP32-based web server. Field testing results demonstrate high accuracy (soil moisture R² = 0.94; temperature ±0.5 °C; humidity ±1.8%), stable system performance (99.8% uptime), and low power consumption (0.9 W), indicating suitability for resource-constrained environments. These findings suggest that the proposed low-cost monitoring system can empower farmers to improve resource-use efficiency, reduce water waste, and enhance crop productivity, while contributing to the advancement of sustainable precision agriculture.